Fostering the Golden Generation 2045: Embedding Pancasila Values in Early Childhood Education - Dian Muhammad Johan Johor Mulaydi; Elly Malihah (Pancasila: Jurnal Keindonesiaan, 2024)
Children represent the nation’s investment and future, destined to become the leaders of tomorrow. Introducing Pancasila values at an early age is essential to nurturing competent individuals with strong character and noble morals. This article explores how integrating Pancasila values in early childhood education can contribute to realizing Indonesia's vision for a “Golden Generation 2045.” Employing a descriptive qualitative approach, this study uses library research methods to gather data. The findings highlight that the incorporation of Pancasila values in early childhood can be effectively achieved through the Merdeka Curriculum, where structured play activities serve as a foundation for learning. By aligning stimulating play with children’s interests, their potential can be fully optimized. Moreover, the Pancasila Ideology Education and Development Book (PPIP) provides a critical resource for enhancing understanding of the Pancasila ideology, ultimately strengthening the nation's cultural resilience and fostering the development of a progressive, modern, and morally grounded society.